An Escape to Pure Existence - LEGENDY, Kristóf (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
In this brief exposition, I embark on an exploration of the essence of values through the lens of 20th-century art. Art, with its inherent lack of definitive utility, offers a fertile ground for multiple interpretations within its designated realm of meaning. Through a retrospective analysis spanning two centuries of cultural evolution, I seek to unravel the drivers behind shifts in Western mentality and lifestyle, particularly the growing detachment from reality in secular societies, moving towards a realm of pure existence. Enriched with theological and philosophical references, my discourse encourages readers to extract insights from various cultural domains. I frame the human experience within four conceivable stages of interaction between existence and reality, advocating for the fourth stage as my preferred state – one that achieves harmony between existential challenges and moral imperatives, fostering a balance between needs and ethical obligations.